Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1364/oe.23.013141
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limit: investigation of hydrodynamic forces on a trapped particle kicked by a laser pulse

Abstract: We introduce a new optical technique where a train of short optical pulses is utilized to disturb a trapped microscopic particle. Using fast (250 kHz) and accurate (nm) detection of the position of the particle, accurately synchronized to the repetition rate of the laser pulses, we can coherently superimpose the displacement caused by each individual laser pulse. Thereby we are able to both bypass the influence from the Brownian motion of the trapped particle and to simultaneously increase the ability to local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies showed the magnitude of the scattering force also linearly increased with A (Fig. S1b) [43]; and its influencing range was roughly the size of the laser beam [42]. Although the scattering force was in z-direction, in our case of 2D confined system, the particle collided with the glass substrate frequently and thus generated significant xycomponent of the force.…”
Section: Supplementary Information For "Probing the Local Re-sponse O...mentioning
confidence: 49%
See 2 more Smart Citations
“…Previous studies showed the magnitude of the scattering force also linearly increased with A (Fig. S1b) [43]; and its influencing range was roughly the size of the laser beam [42]. Although the scattering force was in z-direction, in our case of 2D confined system, the particle collided with the glass substrate frequently and thus generated significant xycomponent of the force.…”
Section: Supplementary Information For "Probing the Local Re-sponse O...mentioning
confidence: 49%
“…When the colloidal particles were strictly confined between two glass walls, the pushing force in z-direction will be able to generate xycomponent due to the collisions between the colloidal particles and the glass wall. Moreover, the scattering force was proved to be localized and the magnitude of which was proportional to A [42,43]. The spatial separation between light spots was more than 20 σ s , much larger than the DLS in the deepest non-linear region.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The switching process (on/off) is controlled by blocking the laser output in intervals with a chopper wheel. By applying a post-elimination technique 19,20 for thermal noise based on a lock-in strategy, a force sensitivity of 2.4 fN is obtained. This value is lower than the force sensitivity obtained before in the context of optical tweezers applications in liquids.…”
mentioning
confidence: 99%
“…For the present experimental configuration based on the periodic repetition of a mechanical stimulus, it is possible to bypass the Brownian noise. 20 By averaging the tracked time series with respect to the chopping period, the spatial displacement is revealed with subpixel resolution. In Figure 2 with all the following events.…”
mentioning
confidence: 99%